Про один рідкісний тип амфор римського часу з Тіри - Масюта, Д.О. (Археологія, 2018)
До наукового обігу вводяться фрагменти амфор типуVIII за класифікацією А. Опайца, знайдені в Тірі. Розглядаються питання, пов’язані з їх морфологією, хронологією, ареалом розповсюдження. Робиться припущення про те, що їх надходження у Тіру пов’язане з римською військовою присутністю у місті в ІІ — першій половині ІІІ ст. н. е. The paper deals with the publication of amphorae finds from Tyras classified as the early variant of type VIII according to A. Opaiţ. These vessels are attributed as one of the rarest varieties of the late Roman pottery ware. In Tyras these vessels are represented by several fragments of profile parts. Their center of production has not been localized yet. However judging by the visually distinct features of the clay composition, one can assume that they were made in the Eastern Mediterranean. The morphological features indicate that these amphorae were intended for transportation and storage of wine. The spread area of such vessels is the territory of provinces Moesia Superior and Moesia Inferior. They are very rare in the North Pontic region. The only known sample was found at the “Sovkhoz 10” cemetery located in the vicinity of Chersonesus. Almost all amphorae of this type were found during the excavations of Roman military camps or cities, where Roman soldiers were stationed during the 2nd — 3rd centuries CE. Such a distribution of findings is hardly accidental and may be related to the provision of Roman military contingents. That observation may also apply to Tyras, where the vexillatio was shifted from the Moesia Inferior since the beginning of the 2nd century CE. The Roman military presence in the city is evidenced by the epigraphic and archaeological data. Perhaps, the variety of transport amphorae under study occurred in Tyras together with Roman soldiers from Moesia Inferior when shifting the vexillatio or during further rotations of troops during the 2nd — first half of the 3rd century CE. It is also likely that the wine contained in these vessels was imported from the Lower Danube River region as a result of mediatorial commercial trade. Статья посвящена публикации происходящих из Тиры находок амфор раннего варианта типа VIII по классификации А. Опайца,. Это сосуды одной из наиболее редких разновидностей керамической тары позднеримского времени. В Тире они представлены несколькими фрагментами профильных частей. Центр их производства пока не локализован, однако, судя по визуально различимым особенностям состава керамического теста, можно сделать предположение о производстве этих изделий в Восточном Средиземноморье. Морфологические признаки указывают, что данные амфоры предназначались для транспортировки и хранения вина. Ареал таких сосудов — преимущественно провинции Верхняя и Нижняя Мезия. В Северном Причерноморье они очень редки. Единственный известный экземпляр был обнаружен в могильнике «Совхоз 10», расположенном в округе Херсонеса. Практически все амфоры данного типа были найдены при исследовании римских военных лагерей или городов, где во II—III вв. н. э. дислоцировались римские войска. Такое распределение находок не случайно и может быть связано с обеспечением римских воинских контингентов. Это наблюдение может касаться и Тиры, куда с начала II в. н. э. из Нижней Мезии была выведена вексилляция. Римское военное присутствие в городе засвидетельствовано эпиграфическими и археологическими данными. Возможно, рассматриваемая разновидность амфорной тары попала в Тиру вместе с римскими солдатами из Нижней Мезии при выводе вексилляции или в ходе дальнейших ротаций военных на протяжении II — первой половины III вв. н. э. Также вероятен импорт вина, содержащегося в этих сосудах, из Нижнего Подунавья в результате торговых операций, имевших посреднический характер.